2021
DOI: 10.4236/ojbm.2021.93064
|View full text |Cite
|
Sign up to set email alerts
|

Safety Measurements and Risk Assessment of Coal Mining Industry Using Artificial Intelligence and Machine Learning

Abstract: Safety is a legal requirement of mining industry. Effective safety measurements and risk management can serve the mine administration to lessen the dangers recognized in the mine. Autonomous technologies, such as Artificial Intelligence (AI) and Machine Learning (ML) models have been integrated with the mining industry to ensure a safe working environment since a decade ago in the form of fully unmanned workfaces and mining robots. These autonomous technologies provide effective risk assessment as well as many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The intelligent construction of coal mining enterprises is an important way to realize the high-quality development of the coal industry. Existing literatures ( Matloob, S. et al., 2021 ; Li et al., 2021 ) mainly focus on intelligent technical support for enterprises from the perspective of engineering technology, and most models are based on the assumption of infinite population. This ignores the following two points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intelligent construction of coal mining enterprises is an important way to realize the high-quality development of the coal industry. Existing literatures ( Matloob, S. et al., 2021 ; Li et al., 2021 ) mainly focus on intelligent technical support for enterprises from the perspective of engineering technology, and most models are based on the assumption of infinite population. This ignores the following two points.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary for the government to regulate and control the intelligent construction behavior of coal mining enterprises through policies. The existing research focuses on the technical support for the intelligent construction of coal mines ( Matloob et al., 2021 ; Chen et al., 2021 ; Nguyen et al., 2020 ; Jo et al., 2019 ; Singh et al., 2018 ), and lacks the discussion on the management issues such as policy regulation in the intelligent construction of coal mining enterprises, which also shows the necessity and urgency of this research.…”
Section: Introductionmentioning
confidence: 99%
“…However, automation in the mining industry is not without its risks and set of challenges, especially considering the involvement of humans on some level [142]. AI-based safety measurement and risk assessment of mines [141], and other similar modeling tools play a crucial role in planning and strategizing mine operations and its safety. The use of remote isolation systems for complex systems improves workplace safety standards through remote switching and racking of circuit breakers [117].…”
Section: B Mitigating the Risksmentioning
confidence: 99%
“…Figures 9(c) and 9(d) revealed that the, the main subsidence area is nearly rounded form, with symmetrical development on both sides of strike and dip that reveals subsidence us, its monitoring is essential for the safety and economics of coal mining [45,46]. erefore, risk assessment and management of coal mining using spatiotemporal mobile imaging systems is extremely important for sustainable development [47].…”
Section: Temporal and Spatial Analysismentioning
confidence: 99%